1998
DOI: 10.1016/s0896-6273(00)80651-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in filamin 1 Prevent Migration of Cerebral Cortical Neurons in Human Periventricular Heterotopia

Abstract: Long-range, directed migration is particularly dramatic in the cerebral cortex, where postmitotic neurons generated deep in the brain migrate to form layers with distinct form and function. In the X-linked dominant human disorder periventricular heterotopia (PH), many neurons fail to migrate and persist as nodules lining the ventricular surface. Females with PH present with epilepsy and other signs, including patent ductus arteriosus and coagulopathy, while hemizygous males die embryonically. We have identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
568
0
12

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 805 publications
(592 citation statements)
references
References 54 publications
9
568
0
12
Order By: Relevance
“…We conclude that OPD1, OPD2, FMD and MNS are allelic conditions 12 , which we collectively term 'OPD-spectrum disorders' . All (17 of 17) mutations reported here, in contrast with a small minority (2 of 14) associated with PVNH 3,5,6 , conserve the reading frame and are predicted to produce full-length filamin A. We compared the structure of filamin A and the distribution of mutations in the ABD with selected proteins containing a homologous domain (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We conclude that OPD1, OPD2, FMD and MNS are allelic conditions 12 , which we collectively term 'OPD-spectrum disorders' . All (17 of 17) mutations reported here, in contrast with a small minority (2 of 14) associated with PVNH 3,5,6 , conserve the reading frame and are predicted to produce full-length filamin A. We compared the structure of filamin A and the distribution of mutations in the ABD with selected proteins containing a homologous domain (Fig.…”
mentioning
confidence: 99%
“…After excluding 24 other genes, we examined FLNA. Mutations in FLNA (predominantly nonsense and frameshift mutations but including two missense mutations) lead to the clinically unrelated neuronal migration disorder PVNH 3,5,6 . FLNA comprises 48 exons and encodes a protein of 280 kDa that possesses an N-terminal actin-binding domain (ABD) containing two calponin homology domains (CHD1 and CHD2) and an extended region made up of 24 repeated rod subdomains that bind to multiple proteins (refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22). On the other hand, mutations in FLNA are the only other identified cause of periventricular heterotopia, but unlike ARFGEF2, FLNA is not associated with microcephaly, and it encodes an actinbinding protein 23 . Thus, the current findings emphasize the crucial, if not yet widely recognized, role of vesicular trafficking in human embryonic development and raise the possibility that the enlarging superfamily of ARFGEF proteins may have evolved more specialized and overlapping functions than suspected [2][3][4][5][6] .…”
mentioning
confidence: 99%
“…FLNA mutations can result in lossof-function or alterations in filamin A function (Robertson 2005). The former was seen in bilateral periventricular nodular heterotopia (PVNH) (OMIM: 300049) (Fox et al 1998), and the latter has been reported in OPD-spectrum disorders such as OPD I, OPD II, frontometaphyseal dysplasia and MelnickNeedles syndrome. Genotype-phenotype correlation is relatively clear between Melnick-Needles syndrome and OPD II, but is not always so between OPD I and OPD II.…”
Section: Discussionmentioning
confidence: 99%